Petiole extract chemical analysis to evaluate nutritional status in grapevine - Pino, Paulina Lorena; Callejas, Rodrigo; Razeto, Bruno; Reginato, Gabino (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the relationship between N, P and K concentration in petiole extract, blades and roots, to determine the nutritional status in grapevine. The experiment was done between December 2006 and February 2007. Three fertilization trials with N, P2O5 and K2O in one‑year‑old Vitis vinifera 'Red Globe' plants, grown in containers, were established. Nitrate, phosphate and potassium concentration were evaluated in the petiole extract, and nitrogen, phosphorus and potassium were determined in blades and roots. Petiole extract analysis was more sensitive than blade and root analysis to determine nitrate and nitrogen status. Meanwhile, blade analysis showed better plant response to fertilization with phosphorus and potassium. Petiole extract analysis can indicate the antagonism between nutrients under high doses of fertilization.